Proteomic analysis on mangrove plant Avicennia marina leaves reveals nitric oxide enhances the salt tolerance by up-regulating photosynthetic and energy metabolic protein expression. (15th June 2018) - Shen, Zhi-jun; Chen, Juan; Ghoto, Kabir; Hu, Wen-jun; Gao, Gui-feng; Luo, Mei-rong; Li, Zan; Simon, Martin; Zhu, Xue-yi; Zheng, Hai-lei
Abstract: Avicennia marina (Forsk.) Vierh is one of the most salt-tolerant mangrove species. Our previous study revealed that nitric oxide (NO) enhanced the salt tolerance of A. marina by promoting salt secretion and Na + sequestration under salt stress. However, little is known about the regulation of NO on proteomic profiling for this mangrove species. In this study, we used sodium nitroprusside (SNP), an NO donor, to investigate the regulatory mechanism of NO on salt tolerance of A. marina according to physiological and proteomic aspects. Photosynthesis data showed that the reduction in photosynthesis caused by high salinity treatment (400 mM NaCl) could be partially recovered by addition of SNP (100 μM). Further analysis revealed that the high salinity treatment could induce not only the stomatal limitation but also non-stomatal limitation on photosynthetic reduction, while SNP addition could restore the non-stomatal limitation, implying that the application of SNP was beneficial to the metabolic process in leaves. Proteomic analysis identified 49 differentially expressed proteins involved in various biological processes such as photosynthesis, energy metabolism, primary metabolism, RNA transcription, protein translation and stress response proteins. Under high salinity treatment, the abundances of proteins related to photosynthesis, such as ribulose-phosphate 3-epimerase (RPE, spot 3), RuBisCO large subunit (RBCL, spot 4, 5, 24), RuBisCO activase A (RCA, spot 17, 18) and quinine oxidoreductase-like protein isoform 1 (QOR1, spot 23), were significantly decreased. However, the abundance of proteins such as RBCL (spot 5, 9) and QOR1 (spot 23) were increased by SNP addition. In addition, exogenous NO supply alleviated salt tolerance by increasing the accumulation of some proteins involved in energy metabolism (spot 15), primary metabolism (spot 25, 45, 46), RNA transcription (spot 36) and stress response proteins (spot 12, 21, 26, 37, 43). The transcriptional levels of nine selected proteins were mostly consistent with their protein abundance except spot 46. Overall, the presented data demonstrated that NO has a positive effect on improving salt tolerance in A. marina by regulating the protein abundance involved in photosynthesis, energy metabolism, primary metabolism and stress response.